Sleep Quality and Cognitive Impairments in Children and Adolescents with Post Traumatic Stress Disorder and/or Depressive Symptoms - Barrera-Valencia, Mauricio; Calderon-Delgado, Liliana; Adan, Ana (Journal of clinical medicine, 2025)
Background/Objectives: Sleep and cognitive alterations are common symptoms associated with child Post-traumatic stress disorder (PTSD) and depression (DEP). This study aims to investigate the relationship between sleep disturbances and cognitive alterations in PTSD and DEP. Methods: Using a quantitative, cross-sectional exploratory design, we examined 130 students (106 girls and 24 boys) aged 11 to 16 years (mean age = 12.9, SD = 1.35) from 6th to 8th grade. Twenty-eight participants met the criteria for PTSD, 15 met the criteria for DEP, 43 met the criteria for both PTSD+/DEP+, and 44 served as the control group. Comparative analyses were conducted using the MANOVA and multiple one-way ANOVA tests. Results: The MANOVA test indicated an interaction between cognitive and sleep alterations. Post hoc analysis revealed that sleep patterns were significantly altered among the groups with PTSD, DEP, and PTSD+/DEP+ (F(3, 126) = 16.98, p = 0.001). In contrast, cognitive alterations were most pronounced in PTSD and PTSD+/DEP+ (F(3, 126) = 63.97, p < 0.001). Conclusions: These findings emphasize the impact of PTSD and DEP on cognition and sleep. Potential clinical implications suggest the need for interventions targeting sleep and cognitive alterations. This study underscores the complex relationship among traumatic experiences, depression, and cognitive/sleep alterations.
Keywords: sleep quality; child and adolescent PTSD; neurocognitive alteration; depression